Impacts of Off-Farm Income on Technical Efficiency of Rice Farming: Correction to Bias - Harmini Harmini; Harianto Harianto; Feryanto Feryanto; Netti Tinaprilla; Maryono Maryono (Universitas Negeri Malang, 2022)
Most of Indonesia's rice farming households are small-scale, with farming income equivalent to below the poverty line. Sources of income from outside the farm can be a complement to the low income obtained from farming. The purpose of the study was to analyze the effect of off-farm income on the technical efficiency of rice farming. This study employed secondary data and analyzed using the stochastic production frontier model, with corrections for the bias associated with the observed and unobserved variables first. This study showed that the education level of the head of the household had a significant positive effect on the opportunity to obtain off-farm income. Land area and fertilizer have a significant effect on increasing rice farming production. Rice farming in the household group without off-farm income has a relatively higher level of technical efficiency than the household group with off-farm income. Therefore, government policies regarding farmers' access to land and fertilizers are needed to increase rice production. Opportunities for farm households to obtain off-farm income will be even greater if policies enable them to obtain a better education.